Globalisation and the incorporation of sustainable development in Malaysian Higher Education. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2008)
There exists a general consensus on the legitimacy of globalisation as a powerful influence in promoting and strengthening the provision of higher education in many countries, notably in its role to sustain knowledge creation and its contribution to a country’s economic growth. In the context of globalisation and the knowledge economy, there has been a considerable transformation in the attitudes of international organisations towards the importance of higher education in developing countries (Naidoo, 2007). There has been an impressive expansion of cross-border higher education initiatives due to the growing imperative of higher education institutions to internationalise teaching, research and community service in order to enhance their academic excellence and the relevance of their contribution to societies. The growth of market-driven activities has to some extent influenced the following domains: increased demand for higher education, funding provisions for research and development activities, access and equity, academic freedom and innovative methods of teaching and learning. Arguably, these activities and transformations create new challenges and intensify existing ones in terms of issues concerning the scope, complexity and volume of higher education.